1988
DOI: 10.2105/ajph.78.9.1232
|View full text |Cite
|
Sign up to set email alerts
|

Health problems of homeless children in New York City.

Abstract: We reviewed the outpatient medical records of 265 homeless children less than 5 years of age in New York City and compared them with children of similar low socioeconomic status (SES) attending the same pediatric clinic. The frequency of health problems among the homeless children, including delayed immunizations, elevated blood lead levels, the rate of admission to hospital, and the rate of child abuse and neglect reports, exceeded those for the comparison groups. (Am J Public Health 1988; 78:1232-1233

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(37 citation statements)
references
References 2 publications
1
36
0
Order By: Relevance
“…25 Immunization status differs by income level; families with lower incomes compared to others are less likely to have age-appropriate immunizations. [26][27][28][29][30][31][32] Among low income families, those living in the most difficult situations such as being transient, in foster care, or living in homeless circumstances are even more likely to have children who lack upto-date immunizations. 28,33,34 Thus, the question remains-why are low-income families relying on emergency rooms for non-urgent care and not engaging in primary health care practices such as immunizations?…”
Section: Health Care Utilization: Emergency Room Use and Immunizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Immunization status differs by income level; families with lower incomes compared to others are less likely to have age-appropriate immunizations. [26][27][28][29][30][31][32] Among low income families, those living in the most difficult situations such as being transient, in foster care, or living in homeless circumstances are even more likely to have children who lack upto-date immunizations. 28,33,34 Thus, the question remains-why are low-income families relying on emergency rooms for non-urgent care and not engaging in primary health care practices such as immunizations?…”
Section: Health Care Utilization: Emergency Room Use and Immunizationsmentioning
confidence: 99%
“…10,27,28,[42][43][44][45][46][47] These characteristics and experiences influence the community culture, physical and social environment, and ultimately the quality of life.…”
Section: Individual-level Indicators (Quality Of Life)mentioning
confidence: 99%
“…11,[13][14][15][16][17][18][19][20] Similarly, characteristics from the neighborhood culture or social environment may be associated with health status or utilization. 21,22 However, few instruments measure neighborhood culture or social environment; consequently, the impact of social and physical neighborhood environments on health care utilization and status is rarely examined.…”
Section: Social Environmentmentioning
confidence: 99%
“…In one study, 52% of homeless mothers reported that "child problems" were a frequent source of stress for them (second only to housing problems) (Banyard, 1995). Higher rates of child abuse and neglect have been reported for homeless families than for low-income housed families (Alperstein, Rappaport, & Flanigan, 1988).…”
Section: Relationships Within Homeless Familiesmentioning
confidence: 99%